"It's our little secret … an in-group, where everyone's in": Females' motives for participation in a stigmatized form of physical activity. (May 2018) - Nicholas, Joanna C.; Dimmock, James A.; Donnelly, Cyril J.; Alderson, Jacqueline A.; Jackson, Ben
Abstract: Objectives: The factors that encourage participation in 'traditional' exercise pursuits are relatively well understood; less is known, however, about the psychological motives that encourage female participation in forms of physical activity that are stigmatized. Using pole dancing as an exemplar of such an activity, the aim of this study was to identify females' participation motives for this activity. Design: Guided by an interpretivist approach, a qualitative method was adopted to allow a group of female pole dancers to describe their reasons for participation. Method: Semi-structured focus group interviews were conducted with 38 recreational through to regularly competitive adult female pole dancers ( M age  = 31.24, SD  = 8.41). Data were content analyzed using inductive thematic principles. Results: Stigma-related issues emerged as a driver of participation. Participants also described motives pertaining to themes of relatedness, autonomy, competence, and intrinsic motivation, as well as new stimuli and mental and physical wellbeing. Conclusion: Despite the stigma and negative stereotypes associated with participation in activities such as pole dancing, participants described how this perception contributed to a heightened sense of community that, in part, drove continued participation. Accordingly, these findings make a novel contribution to established bodies of literature grounded in stigma and optimal distinctiveness theory. Given the rise in popularity of some female-predominant stigmatized exercise pursuits (e.g., belly dancing, roller derby, lingerie football), research that examines this network of motives in other settings would be valuable in the future. Highlights: Examined participation motives among females within a stigmatized and non-mainstream exercise pursuit (i.e., pole dancing). Negative stereotypes associated with the activity appeared to contribute to togetherness and ongoing participation. Participation motives were also associated with the niche, non-mainstream nature of the activity. These findings may inform novel physical activity promotion strategies for females.